O DESAFIO DE UM GRUPO DE ALUNOS DE MESTRADO EM BUSCA DE UM VIVER SAUDÁVEL - Rosangela Maria Fenilli; Odaléa Maria Brüggemann; Maria Emilia de Oliveira (Universidade Federal de Goias, 2001)
This work shows how students of UFSCs Masters Course in Nursing Assistance, 96/1 class, succeeding in keeping the group together and mentally healthy during the elaboration phase of the conclusions course work. In monthly meetings in locals that were chosen by the group in advance, we had informality and happy moments, with a facing strategy, group integration, experiences exchange and a reinforcement of the self. That even not having all the group participation in the meetings, it has being possible to build a relationship based on friendship, companionship, respect, and the valuing of others, which has been contributing in our healthy living process.